Improved Photoelectrocatalytic Effect of Co(Ii) and Fe(Iii) Mixed Porphyrins on Graphite Paste Electrodes Towards Hydrogen Evolution Reaction - Aguirre-Quintana, M; Aguirre-Quintana, M (Royal Society of Chemistry, 2019)
The use of light in metallic complexes has been widely studied in the photoelectrocatalytic performance of the hydrogen evolution reaction (HER). This reaction produces gaseous hydrogen with potential use as a fuel in clean energy conversion systems, such as fuel cells. In this context, metalloporphyrins have shown remarkable activity in the catalysis of HER, which directly depends on the metallic center of the complex. In order to analyze the electrocatalytic effect of materials composed by a mixture of cobalt and iron octaethylporphyrins over graphite paste electrodes in the study of HER, in the absence and in the presence of light, we use voltammetric techniques to analyze the potential shift. In addition, a characterization of the electrodes by electrochemical impedance spectroscopy is carried out, showing a decrease in the charge transfer resistance of the modified electrodes when they are exposed to light. A determination of gaseous hydrogen produced through the use of this material was carried out by gas chromatography. In this research, the mixture of metalloporphyrins over the graphite paste electrode is more active than the independent complexes and it also improves the electric properties in the presence of light, obtaining gaseous hydrogen in an energy-efficient way. The TON found in this research (8100) is higher than in works performed with other systems, having as advantages stability and easy preparation. © 2019 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.